Use of Bladder Antimuscarinics in Older Adults with Impaired Cognition. Issue 2 (7th November 2016) - Green, Ariel R.; Segal, Jodi; Tian, Jing; Oh, Esther; Roth, David L.; Hilson, Liam; Dodson, Jennifer L.; Boyd, Cynthia M.
Abstract : Objective: To examine the use of antimuscarinics for treating urinary incontinence (UI) in older adults with varying levels of cognition. Design: Cross‐sectional. Setting: National Alzheimer's Coordinating Center from 2005 through 2015. Participants: Community‐dwelling men and women aged 65 and older (N = 24, 106). Measurements: Clinicians and staff evaluated each participant's dementia status during annual in‐person assessments. Participants or their informants reported all medications taken in the 2 weeks before each study visit. Results: Overall, 5.2% (95% confidence interval (CI) = 4.9–5.5%) of the cohort took a bladder antimuscarinic. Participants with impaired cognition were more likely to be taking an antimuscarinic than those with normal cognition. Rates of bladder antimuscarinic use were 4.0% (95% CI = 3.6–4.4%) for participants with normal cognition, 5.6% (95% CI = 4.9–6.3%) for those with mild cognitive impairment, and 6.0% (95% CI = 5.5–6.4%) for those with dementia (p < .001). Of 624 participants with dementia who took antimuscarinics, 16% (95% CI = 13–19%) were simultaneously taking other medicines with anticholinergic properties. Conclusion: Use of bladder antimuscarinics was more common in older adults with impaired cognition than in those with normal cognition. This use is despite guidelines advising clinicians to avoid prescribing antimuscarinics in individuals with dementia because of their vulnerability to anticholinergic‐induced adverse cognitive and functional effects. A substantial proportion of cognitively impaired individuals who took antimuscarinics were simultaneously taking other anticholinergic medications. These findings suggest a need to improve the treatment of UI in individuals with impaired cognition.